Patients' right to know: A scoping review - Inkeroinen Saija; Virtanen Heli; Stolt Minna; Leino-Kilpi Helena (WILEY, 2025)
Aims and objectives: To analyse research-based evidence about patients' right to know from their own perspective to promote ethically high-quality nursing and to identify future research areas.
Background: Patients' right to know is a fundamental right. Although of topical research interest, the current state of scientific evidence on patients' right to know has not been reviewed.
Design: A scoping review according to the methodological framework by Arksey & O'Malley and the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews.
Methods: In June 2022, a literature search was conducted in the Ovid Medline, CINAHL and Cochrane Library databases. The inclusion criteria were peer-reviewed, empirical studies on the right to know with samples comprising adult patients. Data were analysed with inductive content analysis, and methodological quality was assessed with Mixed Methods Appraisal Tool.
Results: Out of 2658 identified reports, 12 were selected for analysis. Based on the results, the research on patients' right to know can be classified into two main content categories: (1) expectations of the right and (2) realisation of the right. In the quality assessment, most of the reports did not meet all the quality criteria, the most common deficits being related to instrumentation and risk of bias.
Conclusions: Research-based evidence on patients' right to know provided a general insight into expectations and realisation of the right to know and not to know. The results indicate a need for continued efforts for novel approaches with high-quality methodological choices in future studies.
Relevance to clinical practice: Nurses make constantly ethical decisions: The findings of this study can be useful for their decision-making and understanding of the patient's perspective on knowledge issues, and therefore, support ethically high-quality patient education.
Patient or public contribution: No direct patient or public contribution to the review.